Lean Six Sigma for small- and medium-sized manufacturing enterprises: a systematic review. Issue 3 (11th February 2019) - Alexander, Paul; Antony, Jiju; Rodgers, Bryan
Abstract : Purpose: The purpose of this paper is to explore the most common themes within Lean Six Sigma (LSS) relating to small- and medium-sized enterprises (SMEs) within manufacturing organisations and to identify the research gaps in the existing literature. Design/methodology/approach: Tranfield et al. 's (2003) systematic review methodology was utilised encompassing three stages: planning, conducting and reporting/dissemination. Findings: The literature revealed that there are many areas in which LSS has been utilised with varying successes. In total, 52 journals have been reviewed and it has been concluded that although LSS is a powerful methodology, there are many gaps that exist in the literature and further research is needed to address these in the field of LSS. Research limitations/implications: The papers included in the systematic review were peer-reviewed papers available in English. Due to these limitations, relevant papers may have been excluded. Moreover, the authors have excluded all conference and white papers for their inclusion in this study. Practical implications: It is vital that LSS practitioners are fully aware of the benefits, limitations and impeding factors when implementing a LSS initiative. Therefore, this paper could provide valuable insights to ensuring maximum value, is obtained from LSS implementation in SMEs. Originality/value: This systematic review identifies research gaps in the current literature and highlighting areas of future research which will be beneficial to many SMEs in their pursuit of value optimisation.